Supporting the development of agroecological business models - Narjes, Manuel Ernesto; Dhehibi, Boubaker; Chege, Christine Gacheri Kiria; Ngoma, Hambulo; Staiger Rivas, Simone (CGIAR System Organization, 2022)
The CGIAR Initiative on Agroecology departs from the premise that agroecological transitions involve the adoption of agroecological innovations (e.g., regenerative farming practices, inclusive business models (BMs) and finance, and participatory guarantee systems), which over time should increase the ability of small-scale producers, enterprises, and other food system actors to equitably partake in and benefit from new business opportunities. Identifying opportunities and challenges of integrating agroecology into a business model also requires getting an overview of the respective enterprise’s most relevant links to food system actors along its value chain (VC), which the initiative is doing through the rapid agroecological value chain analyses (RAVCAs) it is carrying out in its agroecological living landscapes (ALLs).